Copy number variation leads to considerable diversity for B but not A haplotypes of the human KIR genes encoding NK cell receptors - Jiang, Wei; Johnson, Chris; Jayaraman, Jyothi; Simecek, Nikol; Noble, Janelle; Moffatt, Miriam F.; Cookson, William O.; Trowsdale, John; Traherne, James A. (Genome Research, 2012)
The KIR complex appears to be evolving rapidly in humans, and more than 50 different haplotypes have been described, ranging from four to 14 KIR loci. Previously it has been suggested that most KIR haplotypes consist of framework genes, present in all individuals, which bracket a variable number of other genes. We used a new technique to type 793 families from the United Kingdom and United States for both the presence/absence of all individual KIR genes as well as copy number and found that KIR haplotypes are even more complex. It is striking that all KIR loci are subject to copy number variation (CNV), including the so-called framework genes, but CNV is much more frequent in KIR B haplotypes than KIR A haplotypes. These two basic KIR haplotype groups, A and B, appear to be following different evolutionary trajectories. Despite the great diversity, there are 11 common haplotypes, derived by reciprocal recombination near KIR2DL4, which collectively account for 94% of KIR haplotypes determined in Caucasian samples. These haplotypes could be derived from combinations of just three centromeic and two telomeric motifs, simplifying disease analysis for these haplotypes. The remaining 6% of haplotypes displayed novel examples of expansion and contraction of numbers of loci. Conventional KIR typing misses much of this additional complexity, with important implications for studying the genetics of disease association with KIR that can now be explored by CNV analysis.